Baby care through design and technology: development of a system of smart objects for the care of babies during their first year of life - González-Quirós, Josué (2019)
The project consisted in designing a system of smart objects that can contribute to the task of caring for babies in their first year of life. The problem raised was the great need for help that mothers with babies aged between 0 and 12 months have in the development process of their children. In seeking to solve this problem, the needs of mothers and their babies were analyzed to determine the most important aspects that require a solution or that imply a greater burden for the mother. To respond to these needs, a design concept, which serves as a reference for the approach of possible solutions, was established. Based on the concept defined as "dynamic assistance" a series of proposals were developed and one of them chosen as the final pitch. This proposal aims at satisfying the needs of monitoring the health condition of the baby, as well as its entertainment and stimulation, this to ensure the baby’s and the mother’s well-being. Technology serves as a tool in the development of product’s functions.